Ultrafast spectroscopy of biliverdin dimethyl ester in solution: pathways of excited-state depopulation. Issue 35 (27th August 2020) - Liu, Yangyi; Chen, Zhuang; Wang, Xueli; Cao, Simin; Xu, Jianhua; Jimenez, Ralph; Chen, Jinquan
Abstract : Biliverdin and its dimethyl ester derivatives are bile pigments with very low fluorescence quantum yield in solution, but naturally serve as chromophores in far-red fluorescent proteins with three orders of magnitude enhanced fluorescence quantum efficiency. Abstract : Biliverdin is a bile pigment that has a very low fluorescence quantum yield in solution, but serves as a chromophore in far-red fluorescent proteins being developed for bio-imaging. In this work, excited-state dynamics of biliverdin dimethyl ether (BVE) in solvents were investigated using femtosecond (fs) and picosecond (ps) time-resolved absorption and fluorescence spectroscopy. This study is the first fs timescale investigation of BVE in solvents, and therefore revealed numerous dynamics that were not resolved in previous, 200 ps time resolution measurements. Viscosity- and isotope-dependent experiments were performed to identify the contributions of isomerization and proton transfer to the excited-state dynamics. In aprotic solvents, a ∼2 ps non-radiative decay accounts for 95% of the excited-state population loss. In addition, a minor ∼30 ps emissive decay pathway is likely associated with an incomplete isomerization process around the C15C16 double bond that results in a flip of the D-ring. In protic solvents, the dynamics are more complex due to hydrogen bond interactions between solute and solvent. In this case, the ∼2 ps decay pathway is a minor channel (15%), whereas ∼70% of the excited-state population decays through an 800 fs emissive pathway. The ∼30 ps timescale associated with isomerization is also observed in protic solvents. The most significant difference in protic solvents is the presence of a >300 ps timescale in which BVE can decay through an emissive state, in parallel with excited-state proton transfer to the solvent. Interestingly, a small fraction of a luminous species, which we designate lumin-BVE (LBVE), is present in protic solvents.